PENGARUH INVESTASI, TENAGA KERJA, DAN TINGKAT KONSUMSI TERHADAP PERTUMBUHAN EKONOMI DI KOTA PONTIANAK TAHUN 2018 - 2023 - Steven, Steven; Fadli, Mochammad Faisal; Lim, Albert Theriono (Jurnal Ekonomi Integra, 2025)
This study aims to determine whether or not there is an influence of investment, labor, and consumption levels on economic growth. This study uses a quantitative research type. The results of the study indicate that simultaneously the variables of investment, labor, and consumption levels affect economic growth. While partially, the variables of investment, labor, and consumption levels affect economic growth. From the regression results, the R-Squared (R2) value is 0.410. This means that the independent variables are able to explain the variation in economic growth in Pontianak City 41.00% while 59.00% is influenced by variables other than the variables in this study.